WLAN environment for indoor localization - Burhan M.F.B.; Shiham N.S.M.; Balasubramaniam N.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Forecasting; Indoor positioning systems; Motion compensation; Nearest neighbor search; Pattern recognition; Access point (APs); Correction algorithms; Indoor environment; Indoor localization; K nearest neighbor algorithm; K-nearest neighbors; Prediction accuracy; Wireless local area networks (WLAN)